2016
DOI: 10.5603/cj.a2015.0063
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation of frequent premature ventricular contractions using ARRAY multi-electrode balloon catheter

Abstract: (Cardiol J 2016; 23, 1: 17-22)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The authors report that an acute RFA success rate was 94%, defined as the elimination of PVCs at the end of the procedure [4]. The rate of acute success rate was very similar to reported by Dubner et al [5]. It should be noted that in Li Zhong et al [4] series, the RFA was done using a 3-dimensional electroanatomic mapping (Carto System, Biosense Webster, Inc., Diamond Bar, California, USA) without any non-contact mapping.…”
Section: Article P 17supporting
confidence: 72%
See 1 more Smart Citation
“…The authors report that an acute RFA success rate was 94%, defined as the elimination of PVCs at the end of the procedure [4]. The rate of acute success rate was very similar to reported by Dubner et al [5]. It should be noted that in Li Zhong et al [4] series, the RFA was done using a 3-dimensional electroanatomic mapping (Carto System, Biosense Webster, Inc., Diamond Bar, California, USA) without any non-contact mapping.…”
Section: Article P 17supporting
confidence: 72%
“…In the current issue of "Cardiology Journal", Dubner et al [5] examined the utility of radiofrequency catheter ablation with a non-contact mapping system EnSite Array™ in patients with frequent PVC.…”
Section: Article P 17mentioning
confidence: 99%
“…Although mostly a young and healthy population, it reflected a challenging ablation group: 12% with structural cardiopathy and more than 80% with no sustained arrythmias to guide the electrophysiological mapping. Despite the fact that other authors have shown the usefulness of NCM-base ablatio in OT VA, 6 its use is not widespread. In fact, the technical challenges and the long learning curve of this system, combined with the development of new catheters and mapping platforms from different manufacturers, have contributed to the recent discontinuation of the 64-pole NCM-guided Ensite Array Balloon.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5 Other antiarrhythmic drugs, such as propafenone, flecainide, and specially amiodarone, have better outcomes, but are associated with adverse side effects. 6 Several studies have demonstrated that radiofrequency (RF) ablation is more efficient than pharmacological therapy for eliminating PVC, especially for refractory symptoms and very frequent PVC. 1---3,5 The number of patients being referred for ablation of OT VA continues to increase, especially earlier in their disease course, due to its efficacy (ranging between 83% and 100%) and safety (overall complication rate: 3.1-5.2%).…”
Section: Introductionmentioning
confidence: 99%
“…Published success rates of RF ablation for VPBs from the RVOT have been excellent and range from 93% to 97.1% [5][6][7] ; however, very few pediatric patients were included in these studies. Further, complication rates published from these investigations focused on acute complications like acute cardiac events or those related to vascular access.…”
Section: Discussionmentioning
confidence: 99%